PESAN-PESAN DAKWAH DALAM NOVEL 172 DAY KARYA NADZIRA SHAFA - Riri Fitriani; Eti Efrina; Siti Misbah (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2024)
ABSTRACT Da'wah messeges become essential elements and greatly determine the success of da'wah implementation. Da'wah is not only conveyed through the pulpit but also through print and electronic media, which can be delivered more easily and have a wider reach. This certainly facilitates humans with print media to seek information such as journals, news, or entertaining readings from short stories, storybooks, or novels. Novels are one of print media that can be used as a medium for da'wah in conveying Islamic teachings. This study aims to determine the da'wah messages in the novel 172 days by Nadzira Shafa. This research uses qualitative research methods with content analysis. The results show that the da'wah messages contained in the novel include messages of faith, moral messages, and also messages about worship (sharia) Keywords : Messages, Da`wah, and Novel